2016
DOI: 10.2147/ijwh.s109819
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a videoconferencing smoking cessation intervention for Korean American women: preliminary findings

Abstract: IntroductionKorean women are reluctant to pursue in-person smoking cessation treatment due to stigma attached to women smokers and prefer treatment such as telephone and online smoking cessation programs that they can access secretively at home. However, there is some evidence that face-to-face interaction is the most helpful intervention component for them to quit smoking.MethodsThis study is a pilot clinical trial that examined the acceptability and feasibility of a videoconferencing smoking cessation interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(83 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…59 The study conducted with Korean American women also reported that those older than 50 years had difficulty operating a video call web application. 32 This study is a pilot clinical trial with the target sample 50, which is not adequately powered. It will help researchers estimate an effect size for future larger studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…59 The study conducted with Korean American women also reported that those older than 50 years had difficulty operating a video call web application. 32 This study is a pilot clinical trial with the target sample 50, which is not adequately powered. It will help researchers estimate an effect size for future larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although statistically insignificant, cotinine-confirmed abstinence rate at 3 months post-quit was approximately 10% higher among Korean American women who received a videoconferencing cessation intervention than among those who received a telephone counseling one. 32 We will determine from this study whether it is worthwhile to pursue videoconferencing smoking cessation interventions as an adjunct to telephone counseling interventions such as quitline service for women who tend to have lower success rates with the service. [23][24][25][26][27]32 The study will also test the feasibility of a home-based salivary cotinine test using a NicAlert test strip.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations